Promoting International Energy Security Volume 2, Turkey and the Caspian - Weiss, Andrew S. (RAND Corporation, 2012)
The Caspian region has a wealth of crude oil and natural gas. Turkey aspires to be a key player in transporting oil and gas from the Caspian area to world markets. This hope is challenged by commercial and regional issues, terrorist threats, and the potential for disruption of tanker traffic in the Bosporus. Helping Turkey build its capacity for pipeline security and maritime disaster response is a promising yet modest area for USAF engagement.